Introducción a la Contabilidad Gerencial - AF192 - 202300 - Ponce De León Pineda, Juan Carlos (2023)
Description: The Managerial Accounting course recognizes the importance of an adequate management information system which facilitates the use of various instruments for decision making. On a daily basis, the senior officials of the leading companies make decisions geared towards meeting short-term goals and achieving strategic objectives, in an environment of competitors with high management standards; also with new technologies that make shorter life cycles of goods and services. The development of the course provides an introduction, to managerial accounting that concentrates on concepts, relationships, and procedures involved in understanding the strategic decision-making process of managers in for-profit business Purpose: The Managerial Accounting course has been designed with the purpose of formulating a management information system that facilitates the use of adequate instruments for decision making.